Is there any alternative to standard chest compression techniques in infants? A randomized manikin trial of the new “2-thumb-fist” option - Ladny, Jerzy R.; Smereka, Jacek; Rodríguez-Núñez, Antonio; Leung, Steve; Ruetzler, Kurt; Szarpak, Lukasz (Medicine (Baltimore), 2018)
Pediatric cardiac arrest is a fatal emergent condition that is associated with high mortality, permanent neurological injury, and is a socioeconomic burden at both the individual and national levels. The aim of this study was to test in an infant manikin a new chest compression (CC) technique ("2 thumbs-fist" or nTTT) in comparison with standard 2-finger (TFT) and 2-thumb-encircling hands techniques (TTEHT). This was prospective, randomized, crossover manikin study. Sixty-three nurses who performed a randomized sequence of 2-minute continuous CC with the 3 techniques in random order. Simulated systolic (SBP), diastolic (DBP), mean arterial pressure (MAP), and pulse pressures (PP, SBP-DBP) in mm Hg were measured. The nTTT resulted in a higher median SBP value (69 [IQR, 63-74] mm Hg) than TTEHT (41.5 [IQR, 39-42] mm Hg), (P < .001) and TFT (26.5 [IQR, 25.5-29] mm Hg), (P <.001). The simulated median value of DBP was 20 (IQR, 19-20) mm Hg with nTTT, 18 (IQR, 17-19) mm Hg with TTEHT and 23.5 (IQR, 22-25.5) mm Hg with TFT. DBP was significantly higher with TFT than with TTEHT (P <.001), as well as with TTEHT than nTTT (P <.001). Median values of simulated MAP were 37 (IQR, 34.5-38) mm Hg with nTTT, 26 (IQR, 25-26) mm Hg with TTEHT and 24.5 (IQR,23.5-26.5) mm Hg with TFT. A statistically significant difference was noticed between nTTT and TFT (P <.001), nTTT and TTEHT (P <.001), and between TTEHT and TFT (P <.001). Sixty-one subjects (96.8%) preferred the nTTT over the 2 standard methods. The new nTTT technique achieved higher SBP and MAP compared to the standard CC techniques in our infant manikin model. nTTT appears to be a suitable alternative or complementary to the TFT and TTEHT.